Market segmentation: a proposed methodology for associating clients and products in the real estate market - Freitas, Ana Augusta Ferreira de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article proposes a new methodology to analyze market segmentation. Chi-Square Automatic Interaction Detection (CHAID) technique and the proposed approach allow to directly associate consumers and dwelling products, providing support for decision-making related to marketing strategies. An empirical example is analyzed using a database, which contains data obtained in interviews with around 3000 prospective clients while searching for a new home. The statistical association between the two groups, resulting from the application of the proposed methodology, provides more useful results than those previously reported in the literature.